THE IMPACT OF ORGANIZATION CULTURE ON EMPLOYEE ENGAGEMENT FOR LIBRARY OFFICERS IN UNIVERSITAS NEGERI MEDAN - Beatrice Hasian Pakpahan; Onan Marakali Siregar (Jurnal Administrasi Bisnis (JUBIS), 2022)
The purpose of this research is to examine the influence of organizational culture on employee engagement. The populations in this research are library officers of Universitas Negeri Medan. This research uses a non-probability sampling technique with the kind of saturated samples. Data were collected using a survey method and then analyzed by using simple linear regression.The results of the research conducted indicate that the organizational culture (X) has a significant effect on employee engagement (Y).